1909
DOI: 10.1007/bf01935674
|View full text |Cite
|
Sign up to set email alerts
|

Experimenteller Beitrag zur psychischen Urticaria

Abstract: An dem nervSsen @harakter einer Hautver~nderung ist nicht mehr zu zweifeln, wenn die klinische Beobachtung den Beweis erbringt, dal] sie die unmittelbare (z. B. nicht erst durch eine VerdauungsstSrung bedingte) Folge eines psychischen Affektes, einer Gehirnfunktion ist. Als Beweis kommt hier zun~chst wohl nur das Experiment in Betracht~ bei welchem tier psyehische Vorgang veto Uatcrsucher ausgelSst wird nnd die Wirl~ung rasch auf d~e Ursache folgt; die ~ibrigen zahlreichen Beobachtungen yon psychischer Urticar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1925
1925
1982
1982

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…3 A few examples may suffice. Kreibich and Sobotka 9 cite the case of a physician who had from childhood been able to produce urticaria on his arms and trunk "by the strength of his will." They refer to a patient of Kohnstamm's who, under the eyes of the physician, was able to produce an urticarial wheal at any designated spot on his forehead just "by thinking about it," without having previously touched the spot.…”
mentioning
confidence: 98%
“…3 A few examples may suffice. Kreibich and Sobotka 9 cite the case of a physician who had from childhood been able to produce urticaria on his arms and trunk "by the strength of his will." They refer to a patient of Kohnstamm's who, under the eyes of the physician, was able to produce an urticarial wheal at any designated spot on his forehead just "by thinking about it," without having previously touched the spot.…”
mentioning
confidence: 98%
“…11 -13 There is an extensive literature dealing with the psychological aspects of urticaria. Reference may be made to casuistic material reported by Kreibich and Sobotka, 10 Bolton, 3 Stern, 18 Naber, 14 Hansen, 8 Saul and Bernstein, 10 Kaywin, 9 Abramson, 1 Freeman, 4 and to personality studies carried out by Stokes, Kulchar, and Pillsbury, 19 Graham and Wolf, 7 and Wittkower. 20 .…”
mentioning
confidence: 96%
“…As early as 1857, Wilson [1] pointed out the influence of psychological factors related to urticaria, eczema and itching sensations. Kreibich and Sobotka [2] and Sack [3] used hypnosis and found evidence for the psychosomatic aspects of skin diseases. Stokes and Beerman [4] found that psychotherapy was effec tive for treating some skin diseases.…”
Section: Introductionmentioning
confidence: 99%